microRNA-218-5p coordinates scaling of excitatory and inhibitory synapses during homeostatic synaptic plasticity - David Colameo; Sara M. Maley; Jochen Winterer; Waleed ElGrawani; Carlotta Gilardi; Simon Galkin; Roberto Fiore; Steven A. Brown; Gerhard Schratt (Proceedings of the National Academy of Sciences, 2025)
Homeostatic synaptic plasticity (HSP) is a neuronal mechanism that allows networks to compensate for prolonged changes in activity by adjusting synaptic strength. This process is crucial for maintaining stable brain function and has been implicated in memory consolidation during sleep. While scaling of both excitatory and inhibitory synapses plays an important role during homeostatic synaptic plasticity, molecules coordinating these processes are unknown. In this study, we investigate the role of miR-218-5p as a regulator of inhibitory and excitatory synapses in the context of picrotoxin (PTX)-induced homeostatic synaptic downscaling (HSD) in rat hippocampal neurons. Using enrichment analysis of microRNA-binding sites in genes changing upon PTX-induced HSD, we bioinformatically predict and experimentally validate increased miR-218-5p activity upon PTX treatment. By electrophysiological recordings and confocal microscopy, we demonstrate that inhibiting miR-218-5p activity exerts a dual effect during HSD: It occludes the downscaling of excitatory synapses and dendritic spines, while at the same time attenuating inhibitory synapse upscaling. Furthermore, we identify the Neuroligin2 interacting molecule Mdga1 as a direct miR-218-5p target which potentially mediates the effect of miR-218-5p on homeostatic upscaling of inhibitory synapses. By performing long-term electroencephalographic recordings, we further reveal that local inhibition of miR-218-5p in the somatosensory cortex reduces local slow-wave activity during non-rapid-eye-movement sleep. In summary, this study uncovers miR-218-5p as a key player in coordinating inhibitory and excitatory synapses during homeostatic plasticity and sleep. Our findings contribute to a deeper understanding of how neural circuits maintain stability in the face of activity-induced perturbations, with implications for pathophysiology.